The Performance of Physical Education Teachers With Additional Duties In Gajah Mungkur District Semarang City Indonesia - Kurniawan, Aldi; Sulaiman, Sulaiman; Soegiyanto, Soegiyanto (Journal of Physical Education and Sports, 2021)
The reasearch is about formation of a coordinator for an education unit is not known, which causes the performance of physical education teachers to be poor and affects the P.E. learning in elementary schools . This study aims to assess the performance of Civil Servant and Non Civil Servant Physical Education teachers who carry out additional duties n Gajahmungkur District, Semarang City. This study is a qualitative research which employs ethnographic approach. The research subjects were Physical Education Teachers in the Gajahmungkur District area of work for the 2019-2020 academic year, School Principals, and Coleagues of Physical Education Teachers in Gajahmungkur District. The Secondary data sources are in the form of identities and the number of teachers, obtained from documents in the Gajahmungkur sub-district, Semarang City. Data collection instruments used in this study are in the form of observation and interview guidelines, as well as documentation studies. Based on the results of the study, it can be concluded that the performance of P.E. teachers who do not have additional duties is quite good. The performance of P.E. teachers who have additional duties are somewhat good, other additional duties greatly affect the performance of P.E teachers. Therefore, it can be said that the additional duties very burdensome for educators. The suggestions of this study are that the teacher can take the role of a real teacher. Without any obstacles from other duties that are very burdensome for the performance of P.E teachers. The authorities can make this suggestion into an evaluation to provide a reasonable additional duties for a teacher.